Association study between X-linked susceptibility genes and clinical features in Chinese female patients with systemic lupus erythematosus - Shen Li; Dongsheng Di; Xiaoxiao Wu; Linlin Zhang; Ruishan Liu; Qian Huang; Haifeng Pan; Dongqing Ye; Ruixue Leng (Taylor & Francis Group, 2019)
Recent large-scale genetic association studies have identified that several single nucleotide polymorphisms (SNPs) on X chromosome are correlated with risk of systemic lupus erythematosus (SLE) in Chinese population. The aim of this study was to estimate association between these loci and clinical features in female patients with SLE. Six SNPs identified in previous studies were genotyped. Odds ratio (OR) was calculated with adjusting for potential confounding factors. A total of 772 SLE patients were included in the final analysis. The data showed that 3 SNPs (rs5914778, rs3853839 and rs1059702) were marginally associated with several clinical subphenotypes. Furthermore, consistent associations were also found in two independent cohorts. However, the cumulative genetic risk score (GRS) was not associated with clinical manifestations as well as the disease activity index at disease diagnosis. In summary, genetic variants in X-linked genes may be potentially associated with presence of specific clinical feature. Further studies in distinct ethnical populations are required to clarify the association between these loci and presence of SLE clinical features.